ETHNOMATHEMATICS: EXPLORATION OF GEOMETRY CONCEPTS IN TIBAN MOSQUE ARCHITECTURE - Badi'atus Sholikhah; Rosita Dwi Ferdiani; Sri Hariyani (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2025)
This study aims to explore the geometric and cultural concepts embedded within the architecture of the Tiban Mosque in Malang regency, assessing their potential as an ethnomathematical learning medium. Through a qualitative ethnographic approach, this research gathered descriptive data from key informants including residents visiting students, mosque officials, and an ornaments craftsman. The study reveals that the Tiban Mosque, a prominent religious tourism site, embodies rich cultural and mathematical concepts. Its architectural elements reflect a blend of Chinese, Indian, and Arabic cultural influences, while the mathematical aspects encompass various geometric principles, including flat shapes, spatial forms, and geometric transformations. These findings suggest that the Tiban Mosque offers a valuable ethnomathematical learning medium, particularly for geometry concepts relevant to secondary education levels. Furthermore, this study highlights how exploring ethnomathematics can cultivate appreciation and foster cultural preservation in the Malang regency.